Human influences on the present denudation rates of the Paulista Peripheral Depression, Brazil - Fernandes, Alexandre Martins [UNESP]; da Conceição, Fabiano Tomazini [UNESP]; Spatti Júnior, Eder Paulo [UNESP]; Couto Júnior, Antonio Aparecido [UNESP]; Hissler, Christophe; Mortatti, Jefferson (Elsevier, 2020)
Chemical weathering and soil erosion in large or small watersheds are used to understand the effect of evolution processes on the Earth's surface and climate. Currently, human-driven land use changes have substantial effects on landscape changes over a range of temporal and spatial scales. In this context, the Sorocaba River basin, São Paulo State, Brazil, is an ideal study area to assess human influence on the present denudation rates of the Paulista Peripheral Depression (PPD). Twelve fluvial water sample collections were carried out at the Sorocaba River mouth, covering one complete hydrological cycle (Jun/2009 to Jun/2010). In the same period, 46 rainfall events were sampled. All samples were analyzed for dissolved cations, anions and silica, and total dissolved solids (TDS). Total suspended solids (TSS) were measured only in fluvial samples. The export of TDS and TSS occurs mostly during the wet season, accounting for ca. 60% and 87% of the total dissolved solids and total suspended sediment transported in the hydrological cycle studied (2009/2010), respectively. The total annual specific flux of TSS was 74.27 t/km2/year (including soil erosion by agricultural activities), with a small portion being derived from the anthropogenic contributions (ca. 2%). The total annual specific flux of TDS (74.43 t/km2/year) was similar to the TSS, but after the correction of the atmospheric inputs and anthropogenic contributions (ca. 18 and 29%, respectively), this value decreased to 39.35 t/km2/year. The chemical weathering rate was 7.1 m/Myear and this process tended towards monosialitization (RE = 2.6), with an atmospheric/soil CO2 consumption rate of 3.3 × 105 mol/km2/year. The difference between the chemical weathering and soil removal rates (7.1 and 49.6 m/Myear, respectively) indicated that the soil thickness reduction occured in the Sorocaba River basin. The climatic control on chemical weathering and soil removal rates was clearly evidenced, with the highest values of denudation occurring in the wet and hot climatic conditions. However, the chemical weathering processes (RE index) was not sensitive to climatic controls. In order to assess human influence on chemical weathering and soil removal rates in the PPD, the results were compared with other works undertaken in this vast geomorphological province. Even considering the uncertainties associated with a number of data points, the chemical weathering and soil removal rates in the PPD observed in this study were approximately 4 and 7.5-fold higher than these natural denudation rates, respectively, evidencing the effect of recent land use changes on the present denudation rates in the PPD. Thus, this study reinforces the complexity of the human-landscape systems in São Paulo State and increases the values of long-term landscape evolution rates.
Keywords: Brazil; Human-landscape system; Landscape evolution; Water-rock interactions